Urban regeneration in the UK - Jones, Phil ca. 20./21. Jh; Evans, James (SAGE, 2013)
With increased and fully updated content and case study material, this edition continues to provide an engaging, systematic guide to the most dramatic transformation of our urban landscape since post-war reconstruction